Nutritional status, knowledge of nutrition and food habits in school children Estado nutricional, hábitos alimentares e conhecimentos de nutrição em escolares - Bertin R.L.* (2010)
Objective: To study the association between nutritional status with dietary habits and nutrition knowledge of students in the municipality of Indaial, in the Brazilian state of Santa Catarina. Methods: This cross-sectional study evaluated the nutritional status of 259 children aged between eight and ten years old. Children were randomly selected among the 3rd and 4 th grades students of elementary public schools of the city. The evaluation and classification of their nutritional status were based on the body mass index (BMI) and compared to growth charts proposed by the World Health Organization (2007). Dietary habits and nutrition knowledge were analyzed by a self-assessed questionnaire and classified in bad, good or excellent according to the obtained score. Statistical analysis included the chi-square test and binary logistic regression, being significant p<0.05. Results: Among the 256 studied students, 63% had adequate weight for age, 66% good eating habits and 52% good nutritional knowledge. Obesity was significantly associated with good eating habits. The eutrophic students presented good eating habits and appropriate knowledge about nutrition. Conclusions: Most of the school students in the sample were healthy and presented a high prevalence of adequate weight as well as good dietary habits and nutritional knowledge. The obese children reported good knowledge about healthy habits, but do not necessarily practice them.